2020
DOI: 10.3390/molecules25112717
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Lignin via Oxidative Depolymerization with Hydrogen Peroxide: Towards Carboxyl-Rich Oligomeric Lignin Fragments

Abstract: The extraction and characterization of defined and carboxyl-rich oligomeric lignin fragments with narrow molecular weight distribution is presented herein. With regard to the well-known pulp bleaching process, oxidative lignin depolymerization was investigated using hydrogen peroxide in an aqueous alkaline solution (i.e., at T = 318 K, t = 1 h) and subsequent selective fractionation with a 10/90 (v/v) acetone/water mixture. While the weight average molecular weight (MW) of lignin in comparison to the starting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 55 publications
4
11
0
Order By: Relevance
“…It can also be observed that even though the M w decreased initially, the M n seemed to be increased with increasing temperatures in all OKLs when compared to KL ( M n of 1200 g/mol). The increased M n during lignin oxidation was also observed in an earlier study . The variation in the RI responses for all samples at 240 and 270 °C can be observed as a function of time in Figure f,g, and those for all the samples in all reaction parameters can be found in Figure S1 in the Supporting Information.…”
Section: Resultssupporting
confidence: 82%
“…It can also be observed that even though the M w decreased initially, the M n seemed to be increased with increasing temperatures in all OKLs when compared to KL ( M n of 1200 g/mol). The increased M n during lignin oxidation was also observed in an earlier study . The variation in the RI responses for all samples at 240 and 270 °C can be observed as a function of time in Figure f,g, and those for all the samples in all reaction parameters can be found in Figure S1 in the Supporting Information.…”
Section: Resultssupporting
confidence: 82%
“…Structural changes (Figure 2) brought by oxidation (LO 20 compared to L20) are, as follows: the appearance of a shoulder at 1728 cm −1 assignable to unconjugated carbonyl groups; the shift of the aromatic skeletal vibration from 1590 cm −1 to 1601 cm −1 ; a shoulder at 1368 cm −1 specific to C-H deformation; a small shoulder at 1212 cm −1 , indicating C-O vibration in guaiacyl ring; a shift of absorption from 1160 cm −1 (assigned to -SO2-and C-OH) to 1150 cm −1 , and its significant decrease; a shift of C-O-C vibration from 1114 cm −1 to 1106 cm −1 , and its significant decrease. These may indicate depolymerization through the splitting of C-O-C bonds and oxidation leading to carbonyl groups, which is in accordance with the expected effects of mild oxidation [37].…”
Section: Ftirsupporting
confidence: 80%
“…at 1368 cm −1 specific to C-H deformation; a small shoulder at 1212 cm −1 , indicating C-O vibration in guaiacyl ring; a shift of absorption from 1160 cm −1 (assigned to -SO2-and C-OH) to 1150 cm −1 , and its significant decrease; a shift of C-O-C vibration from 1114 cm −1 to 1106 cm −1 , and its significant decrease. These may indicate depolymerization through the splitting of C-O-C bonds and oxidation leading to carbonyl groups, which is in accordance with the expected effects of mild oxidation [37]. Structural changes due to the addition of PMDI to oxidized magnesium lignosulfonate (LO 20 P1, LO 20 P3), as seen in Figure 2, have shown increased shoulder at 1730 cm −1 , indicating carbonyl CO groups in urethane structure; an increase of absorption at 1216 cm −1 (LO 20 P1), which is characteristic for transformation of -NCO groups into urethane structures; an increase of 1105 cm −1 , indicating C-O-C groups, (more visible for LO 20 P3).…”
Section: Ftirsupporting
confidence: 77%
See 1 more Smart Citation
“…However, this step is usually considered a bottleneck in pulp production (Ahmad et al, 2020;Mathias, 1993). Consequently, using part of this residual lignin as a raw material for conversion to added-value products would improve the sustainability of the pulping industry without affecting pulp production and the energy balance of the mill (Junghans et al, 2020;Rodrigues et al, 2018;Silva et al, 2009).…”
Section: Introductionmentioning
confidence: 99%